Tanggung Jawab Sosial Perusahaan Untuk Akademisi Akuntansi - Mira Ismirani Fudsyi; Herru Soerjono; Sakti Muda Nasution; Zen Munawar; Dewi Reniawati (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This research aims to determine the company's responsibility towards research development, especially in the field of accounting. Corporate social responsibility has important implications for accounting academics, especially in the development of sustainable accounting and transparent financial reporting. Accounting academics play a role in developing relevant accounting frameworks, methodologies, and standards to measure, report, and evaluate the social and environmental impacts of corporate activities. Accounting has an important role in integrating sustainability aspects that are outlined in the company's business strategy. Shareholders and stakeholders: have a corporate social responsibility framework for strategic business goals. There is a view of corporate social responsibility in cases related to certain companies and findings from research results. Based on the corporate social responsibility framework, the role of accounting academics is directed at corporate social responsibility activities also assisting in business strategy. The corporate social responsibility measurement framework is a challenge, but opens up various promising avenues for future research in developing a research framework in the field of accounting.